Cooperation between health personnel and schools for the identification and control of dengue - Pablo Cordeiro da Silva; Alberto Mesaque Martins; Virgínia Torres Schall (Universidade de Fortaleza, 2014)
Objective: To analyze the process of cooperation between health personnel and the school in potential dengue vector breeding sites in households. Methods: This is an exploratory and descriptive research using a quantitative and qualitative design. Data were obtained in three visits to 93 households of students from a public elementary school in Teófilo Otoni, MG. The visits were performed every 30 days through the cooperation between health personnel and researchers who identified potential Aedes aegypti breeding sites by using a checklist. A health education campaign was held at the school to foster debate on dengue prevention and vector control. Two visits were performed after the campaign to verify possible changes in the students' households. After that, the health personnel were questioned about their perceptions regarding the participation in the investigation process. Results: It could be observed, during the first visit, that 83 (89.3%) households had some kind of container suitable for the dengue vector breeding. During the second and third visits - after the health education campaign - the number of households with potential breeding sites decreased to 65 (70%) and 63 (68%) respectively, showing the important role of such campaigns in the vector control. Conclusion: The study shows the power of health education campaigns developed by health personnel in cooperation with elementary public schools to foster intersectoral actions for dengue prevention. doi:10.5020/18061230.2013.p404